Structural and functional properties of soy protein isolate and cod gelatin blend films - Denavi, Gabriela Alejandra (2009)
The structure-function relationship of composite films obtained from soybean-protein isolate (SPI) and cod gelatin was studied. Films with different ratios of SPI:gelatin (0, 25, 50, 75, 100% [w/w]) and plasticized by a mixture of glycerol and sorbitol were prepared by casting. Regardless of the soybean-protein concentration, the thickness and water-vapor permeability of the composite films diminished significantly as compared to pure-gelatin films. The formulation containing 25% SPI: 75% cod-skin gelatin had the maximum force at the breaking point, which was 1.8-fold and 2.8-fold greater than those of 100% gelatin and 100% SPI films, respectively. Moreover, this formulation offered high percent-deformation values lower than those of gelatin but higher than all other films containing SPI-, and the same relatively low water-vapor permeability as the 100% SPI film. While all the films exhibited high water solubility, a slight reduction in film solubility and soluble protein was observed with increasing SPI concentration. Differential-scanning calorimetry analyses revealed that gelatin was completely denatured in all films, while soy proteins largely maintained their native conformation. Analysis by fourier-transform–infrared spectroscopy revealed that the presence of 25% SPI produced gelatin conformational changes, self-aggregation of gelatin chains, and intermolecular associations via Cdouble bondO bonds between gelatin and SPI proteins. All films were translucent in appearance, but the yellowish color increased with increasing proportions of the soybean proteins.